The Influence of the Creative Economy Ecosystem on the Formation of Young Entrepreneurial Startups - Saripah Saripah; Darwati Susilastuti (Pelopor Publikasi Akademika, 2026)
The creative economy has become a leading sector in Indonesia, contributing 7.8% to national GDP in 2023 and absorbing more than 22 million workers. Despite this potential, Indonesia's young-entrepreneur ratio remains low at 3.47%, or about 6.1 million of the total population, far behind neighboring countries such as Singapore (8.5%) and Malaysia (4.7%). This research analyzes the influence of the creative economy ecosystem on the formation of young entrepreneurial startups in Indonesia. The creative economy has become a leading sector contributing 7.8% to national GDP in 2023 and absorbing more than 22 million workers. Despite this, Indonesia's young-entrepreneur ratio remains low at 3.47%, or about 6.1 million of the total population. The research method used a quantitative approach and survey techniques to examine 300 young entrepreneurs in Jakarta, Surabaya, and Bandung. Data analysis uses structural equation modeling to examine the relationships among variables in the creative economy ecosystem and startup formation. The results show that the creative economy ecosystem has a positive and significant effect on the formation of young entrepreneurial startups, with an R² of 74.2%. Digital technology and business incubator factors are the most dominant drivers of startup formation. This study recommends strengthening digital infrastructure and developing business incubation programs to improve the quality of young entrepreneurs in Indonesia